Memories of when Abib was still Zé Antonio - de Rose, Julio C.; Galvão, Olavo F. (Perspectivas em Análise do Comportamento, 2023)
This text, dedicated to our dear José Antonio Abib, recovers memories from when we met him at the undergraduate program in psychology at the University of Brasilia, when he was still known as Zé Antonio, conducted experimental research with non-human animals, but already had the erudition and interest on philosophical and conceptual issues that eventually matured in the Abib, a researcher who published remarkable books and articles and trained brilliant disciples, contributing to turn Brazil into what is possibly the leading center of the philosophy of Behaviorism in the world.